Human papillomavirus prevalence, genotype distribution, risk factors, and cervical pathology association in women aged 50 years and older: a retrospective cross-sectional study in Xinjiang, China - Li, Nan; He, Li; Zhang, Huabin; Turson, Gulimire; Lou, Jiaqi; Cheng, Hongfang (Frontiers in Oncology, 2026)
BackgroundPersistent high-risk human papillomavirus (HPV) infection is the primary cause of cervical cancer, but epidemiological data on HPV in women aged ≥50 years—especially in ethnically diverse, resource-limited regions such as Xinjiang, China—remain insufficient. Older women face underrecognized risks due to age-related immune decline and inadequate screening, highlighting the need for targeted research.MethodsA retrospective cross-sectional study was conducted among 640 women aged ≥50 years who underwent cervical HPV testing at a tertiary hospital in Kuqa, Xinjiang, from January 2024 to March 2025. A priori sample size calculation indicated a minimum requirement of 544 participants, which was exceeded. Sociodemographic (age, education), behavioral (sexual activity frequency, smoking and alcohol use), and clinical variables (age at menopause, parity, history of cervical surgery, body mass index [BMI]) were extracted from medical records. HPV status and genotypes were detected using a PCR-based DNA microarray, and cervical pathology was classified according to WHO criteria. Statistical analyses were preceded by assessment of variable normality. Analyses included descriptive statistics, binary and ordinal logistic regression, chi-square tests, t-tests/ANOVA, and point-biserial correlation analysis (SPSS 26.0; p<0.05).ResultsThe overall HPV prevalence was 20.6% (132/640), with high-risk genotypes HPV16 (29.5%), HPV53 (18.2%), and HPV58 (12.1%) being the most prevalent. Binary logistic regression showed that a history of cervical surgery (e.g., conization) was strongly associated with a reduced likelihood of HPV positivity (OR=0.015, 95% CI: 0.008--0.028, p<0.001). Univariate analysis indicated that sexual activity frequency was higher in HPV-positive than HPV-negative women (2.35 ± 1.14 vs. 2.11 ± 1.10, t=2.225, p=0.026), but this association was not significant in the multivariate model (OR=1.020, 95% CI: 0.796--1.307, p=0.874). Point-biserial correlation analysis revealed a negative association between HPV positivity and BMI (r_pb=-0.088, p<0.05). HPV-positive women had a higher rate of cervical intraepithelial neoplasia (CIN) and squamous cell carcinoma (SCC) compared with HPV-negative women (31.1% vs. 1.2%, p<0.001). A post hoc power analysis for the cervical surgery–HPV association yielded a power >99.9%.ConclusionWomen aged ≥50 years in Xinjiang have a non-negligible HPV prevalence, with HPV16 and HPV53 as dominant genotypes. A history of cervical surgery was associated with a markedly lower likelihood of HPV detection in this cross-sectional analysis. The association between sexual activity frequency and HPV status was not consistent across analyses and requires cautious interpretation. HPV positivity was strongly correlated with cervical pathological lesions, emphasizing the urgency of tailored screening and prevention strategies for this population.